Competitive Marketing Strategies In Madrasah Tsanawiyah Al-Amiriyah: Balancing Traditional Values And Digital Technology - Prayoga, Aden; Husain, Muhammad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study examines the transformation of marketing at Madrasah Tsanawiyah Al-Amiriyah Banyuwangi through the integration of traditional Islamic values and digital technology to enhance competitiveness. This study aims to explore how Islamic values can be integrated with digital innovation to improve the attractiveness and operational efficiency of the madrasah. A qualitative case study design was employed, with data collected through interviews with school leaders, teachers, staff, and parents, as well as direct observations of digital practices, including the Si Santri application and social media use, and document analysis. Thematic analysis with triangulation ensures data validity. The results indicate that the integration of Islamic teachings based on local wisdom with digital platforms improves the public image and administrative performance of madrasahs. However, this study also highlights challenges, including limited digital skills among staff and concerns about the preservation of traditional values. This research contributes to Islamic education management by offering a contextual model for marketing transformation. Practically, these findings provide strategic insights for Islamic schools and policymakers to develop relevant and identity-based innovations in the digital age, enabling madrasahs to remain competitive while maintaining their religious and cultural foundations